CORPORATE CRIMINAL LIABILITY POST ELIMINATION OF COAL FABA WASTE STATUS FROM B3 WASTE CATEGORY IN INDONESIA - Nur Hidayah Febriyani; Hartiwiningsih Hartiwiningsih (Jurnal Hukum, 2022)
This study analyzes legal issues related to the elimination of fly ash and bottom ash (FABA) coal waste status from the hazardous and toxic waste category (B3) as a result of the promulgation of Governor Regulation No. 22 of 2021 on the Implementation of Environmental Protection and Management. This applied prescriptive study aims to explain the consequences of the legal policy on the concept of corporate criminal liability when corporation is committing criminal acts in the field of coal FABA waste management in Indonesia, which now is no longer belonged to the hazardous and toxic waste category (B3). The result showed that the implementation of penal sanctions on coal FABA waste management throughout 2014 to 2020 did not show any significant restoration nor reclamation in the location of contaminated area. At this time, the concept of coal FABA waste management mechanism which is no longer use strict B3 waste standards potentially raise problems related to environmental sustainability threats in the power plant zone. Moreover, the provisions of Article 88 UUPPLH is unapplicable to FABA waste corporate liability. This legal research belongs to normative legal research with statutory approach, conceptual approach. Data collection techniques are carried out with library study methods.Â